Comparison of Physicochemical Surface Conditioning Methods for Adhesion of bis-GMA Resin Cement to Particulate Filler Composite and Surface Characterization - Oezcan, Mutlu; De Araujo Michida, Silvia M. [UNESP]; Sipahi, Cumhur; Souza, Rodrigo O. A.; Lombardo, Geraldo [UNESP]; Takahashi, Fernando E. [UNESP]; Nascente, P. [UNESP] (Taylor & Francis Ltd, 2014)
This study compared the effect of physicochemical surface conditioning methods on the adhesion of bis-GMA-based resin cement to particulate filler composite (PFC) used for indirect dental restorations. PFC blocks (N (block)=54, n (block)=9 per group) were polymerized and randomly subjected to one of the following surface conditioning methods: a) No conditioning (Control-C), b) Hydrofluoric acid (HF)etching for 60s (AE60), c) HF for 90s (AE90), d) HF for 120s (AE120), e) HF for 180s (AE180), and f) air-abrasion with 30 mu m silica-coated alumina particles (AB). The conditioned surfaces were silanized with an MPS silane, and an adhesive resin was applied. Resin composite blocks were bonded to PFC using resin cement and photo-polymerized. PFC-cement-resin composite blocks were cut under coolant water to obtain bar specimens (1mmx0.8mm). Microtensile bond strength test (mu TBS)was performed in a universal testing machine (1mm/min). After debonding, failure modes were classified using stereomicroscopy. Surface characterization was performed on a set of separate specimen surfaces using Scanning Electron Microscopy (SEM), X-Ray Dispersive Spectroscopy (XDS), X-Ray Photoelectron Spectroscopy (XPS), and Fourier Transform-Raman Spectroscopy (FT-RS). Mean mu TBS (MPa) of C (35.6 +/- 4.9) was significantly lower than those of other groups (40.2 +/- 5.6-47.4 +/- 6.1) (p<0.05). The highest mu TBS was obtained in Group AB (47.4 +/- 6.1). Prolonged duration of HF etching increased the results (AE180: 41.9 +/- 7), but was not significantly different than that of AB (p>0.05). Failure types were predominantly cohesive in PFC (34 out of 54) followed by cohesive failure in the cement (16 out of 54). Degree of conversion (DC) of the PFC was 63 +/- 10%. SEM analysis showed increased irregularities on PFC surfaces with the increased etching time. Chemical surface analyses with XPS and FT-RS indicated 11-70% silane on the PFC surfaces that contributed to improved bond strength compared to Group C that presented 5% silane, which seemed to be a threshold. Group AB displayed 83% SiO2 and 17% silane on the surfaces.
Keywords: Microtensile bond strength; Adhesion; Direct composite resin; Indirect compositeresin; XPS; FT-RS; XDS